Randomized, controlled trial of Interpersonal and Social Rhythm Therapy for young people with bipolar disorder. (24th October 2014) - Inder, Maree L; Crowe, Marie T; Luty, Suzanne E; Carter, Janet D; Moor, Stephanie; Frampton, Christopher M; Joyce, Peter R
<x xml:space="preserve">Abstract</x> Objective This randomized, controlled clinical trial compared the effect of interpersonal and social rhythm therapy (IPSRT) to that of specialist supportive care (SSC) on depressive outcomes (primary), social functioning, and mania outcomes over 26–78 weeks in young people with bipolar disorder receiving psychopharmacological treatment. Methods Subjects were aged 15–36 years, recruited from a range of sources, and the patient groups included bipolar I disorder, bipolar II disorder, and bipolar disorder not otherwise specified. Exclusion criteria were minimal. Outcome measures were the Longitudinal Interval Follow‐up Evaluation and the Social Adjustment Scale. Paired‐sample t‐tests were used to determine the significance of change from baseline to outcome period. Analyses of covariance were used to determine the impact of therapy, impact of lifetime and current comorbidity, interaction between comorbidity and therapy, and impact of age at study entry on depression. Results A group of 100 participants were randomized to IPSRT (n = 49) or SSC (n = 51). The majority had bipolar I disorder (78%) and were female (76%), with high levels of comorbidity. After treatment, both groups had improved depressive symptoms, social functioning, and manic symptoms. Contrary to our hypothesis, there was no significant difference between therapies. There was no impact of lifetime or current Axis I comorbidity or age at study entry. There was a relative impact of SSC for patients with current substance use disorder. Conclusions IPSRT and SSC used as an adjunct to pharmacotherapy appear to be effective in reducing depressive and manic symptoms and improving social functioning in adolescents and young adults with bipolar disorder and high rates of comorbidity. Identifying effective treatments that particularly address depressive symptoms is important in reducing the burden of bipolar disorder.